Drug-induced Parkinson-like events: a real-world study from 2004 to the first quarter of 2024 based on FAERS - Ke Wang; Ke Wang; Junyan Chen; Mingquan Huang; Xinhao Zeng; Xiaoqun Ren; Xiuqiong Liu; Chao Tao; Chao Tao; Liuxuan Yang; Liuxuan Yang; Jinlu Shang; et al. (Frontiers in Pharmacology)
BackgroundTimely identification of drug-induced Parkinson-like events is essential to improve clinical management and enhance patients’ quality of life. However, there is a significant lack of studies addressing these events in real-world settings.MethodsTo bridge this gap, we analyzed adverse event (AE) reports related to Parkinson-like events from the FDA Adverse Event Reporting System (FAERS) database from the first quarter of 2004 to the first quarter of 2024. Our objective was to summarize a list of potential drugs at high risk for Parkinson-like events and their corresponding proportions of AE reports.ResultsAs a result, a total of 54,639 AE reports linked to Parkinson-like events involving 1,224 drugs were identified. Among these, carbidopa/levodopa exhibited the highest number of reports, followed by baclofen and pimavanserin. The most frequently reported drug class was antiparkinsonian drugs and psycholeptics, followed by psychoanaleptics. Using two disproportionate analysis methods, the reporting odds ratio and proportional reporting ratio, we found that 136 drugs exhibited positive results in both methods, while 1,063 drugs did not show any positive signals.ConclusionThis study provides a comprehensive pharmacovigilance analysis of drugs associated with Parkinson-like events, aiming to promote rational drug use and inform clinical practice.